Reduced axonal diameter of peripheral nerve fibers in a mouse model of Rett syndrome. (1st September 2017) - Bahey, Noha G.; Gadalla, Kamal K.E.; McGonigal, Rhona; Bailey, Mark E.S.; Edgar, Julia M.; Cobb, Stuart R.
Graphical abstract: Highlights: A mouse model of Rett syndrome reveals a reduced diameter of peripheral myelinated nerve fibers. Mitochondrial densities per unit area of axoplasm are significantly altered in Mecp2 +/− mice. There is no detectable change in mitochondrial integrity or nerve conduction properties between Mecp2 +/− and wild-type mice. Abstract: Rett syndrome (RTT) is a neurological disorder characterized by motor and cognitive impairment, autonomic dysfunction and a loss of purposeful hand skills. In the majority of cases, typical RTT is caused by de novo mutations in the X-linked gene, MECP2 . Alterations in the structure and function of neurons within the central nervous system of RTT patients and Mecp2 -null mouse models are well established. In contrast, few studies have investigated the effects of MeCP2-deficiency on peripheral nerves. In this study, we conducted detailed morphometric as well as functional analysis of the sciatic nerves of symptomatic adult female Mecp2 +/− mice. We observed a significant reduction in the mean diameter of myelinated nerve fibers in Mecp2 +/− mice. In myelinated fibers, mitochondrial densities per unit area of axoplasm were significantly altered in Mecp2 +/− mice. However, conduction properties of the sciatic nerve of Mecp2 knockout mice were not different from control. These subtle changes in myelinated peripheral nerve fibers in heterozygous Mecp2 knockout mice could potentially explain some RTT phenotypes.